Energy recovery from natural gas pressure reduction stations: Integration with low temperature heat sources. (1st March 2018) - Borelli, Davide; Devia, Francesco; Lo Cascio, Ermanno; Schenone, Corrado
Graphical abstract: Highlights: Energy can be recovered by pressure drop in natural gas pressure reduction stations. Reducing the process temperature enables integration with low enthalpy heat sources. Temperature lowering does not lead to hazardous system operation. Higher investment costs are balanced by increased saving from thermal integration. Abstract: Energy recovery from Natural Gas (NG) distribution networks is a promising strategy in order to pursue energy sustainability in urban areas. The NG pressure reduction process, normally achieved by means of conventional throttling valves, can be upgraded by implementing turbo expander technology, which allows recovery of energy from the NG pressure drop. As commonly known, in this process the NG must be preheated in order to avoid methane-hydrate formation. The preheating temperature represents a key parameter of the process, on which depends the possibility of integrating low enthalpy heat sources into the system and of exploiting more efficient technologies and renewable energies as well. In this work, the possibility of integrating a pressure reduction station with low temperature heat sources is studied. In particular, a novel plant configuration consisting of a two-stage expansion system is presented and its energy performances are investigated by means of numerical dynamic simulations. The risk of formation of methane hydrate is assessed for different operating conditions and for transient behavior. Finally, the energy efficiency of PRSs with high and low temperature configuration is compared, showing how the two stage expansion can achieve higher energy performance and be effectively integrated with low enthalpy heat sources.